Professional Qualification of German Physicians in Medical Informatics - Michaelis, J. (Methods of Information in Medicine, 1994)
In addition to the medical education in the Federal Republic of Germany which includes a compulsory Medical Informatics course there exists a formal program for professional qualification of physicians in Medical Informatics. After two years of clinical practice and 1.5 years of professional training at an authorized institution, a physician may receive in addition to the medical degree a “supplement Medical Informatics”. The qualification requirements are described in detail. Physicians with the additional Medical Informatics qualification perform responsible tasks in their medical domain and serve as partners for fully specialized Medical Informatics ex-’ perts in the solution of practical Medical Informatics problems. The formal qualification is available for more than 10 years, has become increasingly attractive, and is expected to grow with respect to future Medical Informatics developments.
Keywords: Postgraduate Medical Training; Medical Informatics; Medical Curriculum